Implementasi Program Ta’lim dalam Membina Akhlak Siswa di MTs Swasta Sabila Hamparan Perak - Lutfi Rizal Putra; Zulfiana Herni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Morals are one of the factors that greatly determine the rise and fall of a person, nation or country. In building and fostering the morals of the nation's generation, they have an important role. This study discusses a program called the ta'lim program implemented by one of the schools in Deli Serdang in fostering morals by using the book